Variación de ingresos de la Empresa Inteligencia Security Rmm Cia. Ltda. De la ciudad de Cuenca durante los periodos 2022-2023. - Jiménez Vergara, Dayana Jimena (2024)
The case study focuses on Inteligencia Security RMM Cía. Ltda. located in Cuenca and its financial analysis for the years 2022 and 2023. Despite an increase in revenue in 2023 compared to 2022, the company has struggled to convert this revenue into significant profits. Identifying and addressing these deficiencies is crucial to improving the company's operational and financial efficiency. The main objective of this study is to analyze the variation in the company's revenue during the mentioned periods. Methodologically, a quantitative and descriptive approach was used to detail and describe the results clearly and precisely. Additionally, exploratory research was employed to address the specific problems of the company. The results reveal a significant decrease in ordinary activities revenue, with a notable drop in service provision. In discussing the results, it is concluded that the company needs to review and improve its operational and financial strategies. It is essential to identify and address areas of inefficiency to improve profitability and long-term sustainability. Finally, various actions are recommended, such as identifying and expanding into new markets, conducting internal audits to improve inefficient processes, investing in technologies to reduce costs, and adjusting strategies based on detailed analyses of new revenue categories.